Christian identity, the racialized migrant and the development of virtue: extending Robert Heimburger's account of neighbours and borders. Issue 5 (September 2019) - Adam, Margaret B.
Heimburger's account of Christianity claiming for its own the identity of God's chosen people benefits from attention to the concurrent racialization and displacement of others from desirable land. Faithful discernments about Christian identity and national borders require the communal development and mutual accountability of the cardinal virtues as a penitential response to neighbours in need.